DEVELOPMENT OF THE HIP JOINT AFTER FUNCTIONAL TREATMENT OF CONGENITAL HIP DISLOCATION IN INFANTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The problem of restoring the anatomical integrity and functional fullness of the hip joint in children with various forms of dysplastic changes of congenital etiology is still very relevant, socially significant and difficult to resolve.